Experimental investigation on anisotropic surface properties of crystalline silicon - Shobha Kanta Lamichhane (Bibechana, 2012)
Anisotropic etching of silicon has been studied by wet potassium hydroxide (KOH) etchant with its variation of temperature and concentration. Results presented here are temperature dependent etch rate along the crystallographic orientations. The etching rate of the (111) surface family is of prime importance for microfabrication. However, the experimental values of the corresponding etch rate are often scattered and the etching mechanism of (111) remains unclear. Etching and activation energy are found to be consistently favorable with the thermal agitation for a given crystal plane. Study demonstrate that the contribution of microscopic activation energy that effectively controls the etching process. Such a strong anisotropy in KOH allows us a precious control of lateral dimensions of the silicon microstructure.